Strain Improvement of Pseudomonas sp for the Production of Lipase - Ilyas*, Rajeshkumar Jayaraman; M.H. Muhammad (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Pseudomonas sp. capable of extracellular lipase production was isolated from rhizosphere soil of paddy fields in Tamilnadu, India. The isolated strain was mutated using ultra-violet rays and chemical agents like Sodium Azide and EMS. The study indicated that the lipase activity of the mutant strain using chemical mutagen was 2-fold higher than the wild strain.